Cross‐cultural adaptation and validation of the Spanish version of the Paediatric Throat Disorders Outcome Test (T‐14). (27th November 2017) - Larrosa, F.; Samara, L.; Esteller, E.; Dura, M.J.; Escamilla, Y.; Alberti, A.; Rosell, R.; Hopkins, C.
Abstract : Objectives: The Paediatric Throat Disorders Outcome Test (T‐14) is a disease‐specific questionnaire that parents are requested to complete; it aimed to assess the quality of life related to tonsil and adenoid disease or its treatment in children with throat disorders. The aim of this study was to validate the Spanish adaptation of the T‐14, thus allowing comparison across studies and facilitating international multicentre projects. Design, setting and participants: This was a multicentre prospective instrument validation study. Guidelines for the cross‐cultural adaptation process from the original English‐language scale into a Spanish‐language version were followed. The psychometric properties (reproducibility, reliability, validity, responsiveness) of the Spanish version ("T‐14‐s" for "T‐14‐Spanish") were assessed in 50 consecutive children undergoing adeno/tonsillectomy (both before and 6 months after surgery) and in a separate cohort of 50 unaffected children in a comparable age range. Main outcome measures and results: Test‐retest reliability (γ = 0.83) and internal consistency reliability (α = 0.94) were adequate. The T‐14‐s demonstrated satisfactory construct validity ( r > 0.40). The instrument showed excellent between‐group discrimination ( P < .0001) and a high responsiveness to change (effect size = 2.09). Conclusions: The Spanish version of the T‐14 (T‐14‐s) is a valid tool for measuring the subjective severity of throat disorders, and its use is recommended.